Relatable Da'wah: Constructing Birrul Walidain Values in Hilman Fauzi’s Digital Discourse - Siti Fatimah; Nirwan Syafrin; Dewi Anggrayni (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study aims to understand how the Akhlak Birrul Walidain values ​​are realized in the digital da'wah content of Ustadz Hilman Fauzi (UHF). Moral degradation and increasing conflict between the younger generation and the older generation in the digital era are exacerbated by the impact of social media. The main focus of this analysis is to examine the representation of Akhlak through three perspective Critical Discourse Analysis (CDA): Text, Discourse Practice, and Sociocultural Practice. The method used is qualitative descriptive analytical CDA, centered on video lectures delivered by UHF. The results show that UHF conveys the concept of birrul walidain with the main approach of 'Relatable Da'wah', a discursive strategy to maintain the relevance of Islamic morality in the public sphere. Textually, this discourse is characterized by pragmatic and non-dogmatic rhetoric, which connects moral obedience with worldly benefits, such as smooth sustenance and inner peace. This research helps redefine religious authority in the digital age by highlighting the shift from dogmatism to 'relatability', providing theoretical contributions to global Islamic communication studies in understanding the negotiation of traditional values ​​on modern platforms